THE APPLICATION OF THE DEPRECIATION METHOD OF FIXED ASSETS AND THE INFLUENCE ON THE PROFIT OF THE COMPANY PT. SUMBER AGRI SEHAT - Dani , Dani; Marpaung, Oktavia (CV. Era Digital Nusantara, 2022)
This study aims to determine the method of depreciation of fixed assets applied by the company at PT Sumber Agri Sehat. To determine the effect of depreciation of fixed assets on profits at PT Sumber Agri Sehat. The type of research used is qualitative with the analytical method used in this study is descriptive method with a quantitative approach, namely an analysis that describes the method of depreciation of fixed assets applied by the company with other depreciation methods such as the double declining balance method and the number of years digits and describes the profit earned. achieved by the company in the form of figures that include financial statements. The results of this study indicate that the fixed asset depreciation method used by the company is the straight-line depreciation method and is appropriate and can generate positive profits. By using the straight-line depreciation method the amount of depreciation expense is smaller than using the double-declining balance method and the sum of the year's digits. The results of the comparison of the fixed asset depreciation method applied by the company affect the company's profit where the use of the depreciation method will have an impact on the greater or the smaller the company's profit.